Are the pens working for justice? News media coverage of renewable energy involving Indigenous Peoples in Canada. (November 2019) - Walker, Chad; Alexander, Alyssa; Doucette, Mary Beth; Lewis, Diana; Neufeld, Hanna Tait; Martin, Debbie; Masuda, Jeff; Stefanelli, Robert; Castleden, Heather
Abstract: Some are suggesting that renewable energy by, for, and in Indigenous communities can provide a vehicle for both Indigenous-settler reconciliation, and climate change mitigation in Canada. Yet very little empirical research aimed at understanding this kind of energy transition has been published to date. In this paper, we present findings from an analysis of five large, mainstream (CBC, Globe and Mail, National Post, Vancouver Sun, Toronto Star) and Indigenous (APTN) Canadian media outlets from 2008 to 2017 (n = 153). Using Etuaptmumk (Two-Eyed Seeing) and energy justice frameworks, we are interested in the ways Indigenous Peoples are being written about and perceived among the Canadian public. We use content analysis to understand more about the types of issues being brought forth into the public eye, and critical discourse analysis to assess each outlet's telling and framing of these stories. Findings indicate that stories of Indigenous opposition to large scale hydro development dominate our sample – articles of protest, lawsuits, and threats to nation-to-nation-building that are more commonly seen in extractive industries. Stories covering other technologies (e.g. solar, wind) showcase excitement, positive socio-economic benefit, and opportunities for reconciliation. Second, and against the backdrop of historical misrepresentation of Indigenous Peoples, we find what some may deem exemplars of fair coverage of Indigenous Peoples and renewable energy. Despite the absence of overt racist phrases — as seen in the recent past — authors rarely attend to the colonial history that has created structural issues prevalent in communities today. In the face of long-standing (energy) injustices, we question how far the coverage goes towards raising alternative and Indigenous perspectives. We close the paper with what we see as potential for future research trajectories to critically consider the role of the news media in addressing nation-to-nation relationships in Canada and other colonized territories.